Re-Thinking Entrepreneurial Orientation and Performance of Small and Medium Enterprises in Kano - GORONDUTSE, ABDULLAHI; Bello Rogo, Halilu; Hassan, Mudassir (Research in Management of Technology and Business, 2023)
Research investigations on entrepreneurial orientation (EO) and performance of small and medium enterprises (SMEs) are enormous in entrepreneurship literature. However, there are few studies that investigated the relationship between EO dimensions – risk-taking, innovativeness, proactiveness, autonomy and competitive aggressiveness. Yet, studies that investigated the relationship in developing country context are limited in entrepreneurship literature. Thus, this research aims to determine whether the five (5) 5 EO – dimensions matter, on the performance of SMEs in Kano, Nigeria. To determine this relationship, quantitative research was adopted and data of 197 SMEs’ managers was collected using questionnaire. Hence, the study is a cross-sectional survey, the data was analyzed using SPSS – statistical package for social science and SEM – Structural Equation Modelling. According to the outcome, competitive aggressiveness, innovativeness and risk-taking matter on the performance of SMEs. While, proactiveness and autonomy do not matter on the performance of SMEs. Therefore, research implications were provided as a guide to policy makers and business managers.